Exodus - Peto, John; Cunningham, Vinny (Ireland : Open Reel Production, 2008)
In 1969 Londonderry's City side, the west bank of the Foyle, was home to approximately 18,000 Protestants. Today fewer than 500 remain. It has been one of the biggest peacetime moves of population in Western Europe. This documentary looks at why and how this migration took place in the course of 35 years. “Exodus” hears the stories of the families who left their homes during these years but records also the words of the people who chose to stay. Using archive footage, the documentary recalls some of the lowest points for Derry during the Troubles which saw the killing of innocent civilians and members of the security forces and looks at how communities were split along sectarian lines. As the IRA spread fear throughout the west bank, the trickle of fleeing men, women and children became a mass exodus and by the 1970s no members of the police force (RUC), could live on Londonderry’s City side.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films